Promising effects of corticosteroid treatment in combination with antifungal agents in a patient with Aspergillus meningitis. Issue 7 (25th July 2022) - Jalali, Parisa Aziz; Lotfali, Ensieh; Rezaei, Kamran; Fatemi, Alireza; Ashrafi, Farzad; Oraee‐Yazdani, Saeed; Mirdehghan, Alimohammad
Abstract: Although Aspergillus meningitis is poorly responsive to current guidelines for treatment, we describe a dramatic response of Aspergillus meningitis in a patient to treatment using a combination of corticosteroids with guideline's suggested antifungal agents. Administration of corticosteroids in patients with Aspergillus meningitis is rarely reported in previous studies. Abstract : Although Aspergillus meningitis is poorly responsive to current guidelines for treatment, we describe a dramatic response of Aspergillus meningitis in a patient to treatment using a combination of corticosteroids with guideline's suggested antifungal agents. Administration of corticosteroids in patients with Aspergillus meningitis is rarely reported in previous studies.